1986
DOI: 10.1051/rnd:19860426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soya protein on digestive enzymes, gut hormone and anti-soya antibody plasma levels in the preruminant calf

Abstract: Summary. The Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
2

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 9 publications
4
19
0
2
Order By: Relevance
“…Total replacement of skim milk proteins by soyabean and fish proteins led to a decrease in the basal plasma concentrations of secretin and GIP. One h after the meal the GIP concentration was still reduced, whilst that of CCK increased (Guilloteau et al, 1986a). Similar trends were observed for secretin and CCK when fish protein hydrolysate was used as the protein source in milk replacer (Guilloteau et al, 1984b(Guilloteau et al, , 1986bZabielski et al, 1998).…”
Section: Effect Of Meal and Its Compositionsupporting
confidence: 70%
“…Total replacement of skim milk proteins by soyabean and fish proteins led to a decrease in the basal plasma concentrations of secretin and GIP. One h after the meal the GIP concentration was still reduced, whilst that of CCK increased (Guilloteau et al, 1986a). Similar trends were observed for secretin and CCK when fish protein hydrolysate was used as the protein source in milk replacer (Guilloteau et al, 1984b(Guilloteau et al, , 1986bZabielski et al, 1998).…”
Section: Effect Of Meal and Its Compositionsupporting
confidence: 70%
“…Calves (Guilloteau et al, 1986) and sheep (Ulbrish et al, 1981), when fed with a milk substitute similar to that used by us, presented plasmatic levels of secretin, both basal and postprandial, always lower than those reported in animals fed maternal milk.…”
Section: Discussionmentioning
confidence: 49%
“…Most of these studies have been carried out using calfs and lambs, and focused on the effects of the partial substitution of milk protein by soyabean protein and on the influence of fat levels in the milk substitutes on exocrine pancreatic secretion (Ternouth et al, 1974(Ternouth et al, , 1975Sedgman et al, 1985). Ternouth et al (1975), Jenkins et al (1980) and Guilloteau et al (1986) have reported decreases in pancreatic secretory response to food intake in both flow rate and proteolytic enzymes in animals fed with a milk-substitute. Discrepant findings have been obtained for pancreatic lipase secretion: whereas Ternouth et al (1975) found that the partial substitution of milk protein by soyabean protein led to an increase in lipase output, Ulbrish et al (1981) reported a fall in lipase activity in the pancreatic secretions of lambs.…”
Section: Introductionmentioning
confidence: 99%
“…In calves, daily quantities of juice, pepsin and electrolytes largely increase; however, those of chymosin decrease [34,44]. These [29,40]. In calves, the outflows of pancreatic fluid, protein and trypsin during 5 h postfeeding were 40 % lower, unchanged and 82 % higher, respectively, when soybean protein was fed as compared to milk protein [72].…”
Section: Effect Of Age On Digestive Productions and Enzyme Expressionsmentioning
confidence: 99%
“…If [72,76]. However, in preruminant calves and in pigs, pre-feeding and/or postfeeding plasma levels of many peptides were highly affected [14,40] [66] and for CCK [18], as well as for the amounts of protein (a amino nitrogen) absorbed for gastrin, glucagon, insulin and PP [107]. Moreover, a modification of the vagally dependent cephalic phase of pancreatic secretion with a soybean diet is noteworthy and is described in preruminant calves [71,102].…”
Section: Effect Of Age On Digestive Productions and Enzyme Expressionsmentioning
confidence: 99%